PEKERJA MISMATCH ANTARGENERASI : PENDEKATAN AGE-PERIOD-COHORT - Jamalludin Jamalludin (Syiah Kuala University, 2021)
Abstract.A massive expansion of education reduces the incidence of undereducation but on the other hand, can trigger overeducation in the job market. Educational achievements, cultural, political, and economic developments also shape the preferences and work ethic of a generation. This study analyzes intergenerational mismatch workers by comparing them at the same age point. Using Sakernas 2000-2015 data, this studysucceeded in capturing mismatched workers in the warrior generation, the old order generation, the new order generation, and the reform generation.This study use unadjusted odds ratio for descriptive analysis and multinominal logit for inference analysis. Multinomial logit findingsshow that the generation of the old order and the generation of fighters tend to have a higher mismatch in their work compared to the generation of the new order. The reformation generation has a lower tendency to mismatch than the new order generation. The difference in the proportion of mismatched workers between generations is getting smaller as they enter the age of 60 and over .